Kajian Semanalisis Hingga Intertekstualitas Julia Kristeva: Analisis atas Teks Al-Quran tentang Eksistensi Hujan - Umi Wasilatul Firdausiyah (Journal of Islamic Civilization, 2021)
Julia Kirsteva is one of the philosophers as well as international intellectuals whose thoughts on the semanalis of the wretched thoughts are in great demand by many intellectuals. This paper examines the semanalysis of Julia Kristeva coupled with a Quranic verse in the form of rain. By following the arrangement of Kristeva's approach, which begins with a semanalytic approach, then the genotex and phenotex are born, followed by the division of the meaning of signifiance and signifying, and the last is to look for the intertextuality of the text being studied. The result of this research is that the meaning related to rain is not the same, which depends on how the reviewer can understand the context and the social and religious relationships that surround it. The existence of rain is basically a gift from Allah, but there are times when Allah admonishes his creation to contemplate His greatness.